Attitude of Vocational and Technical Education Lecturers Towards Utilization of Open Educational Resources for Effective Teaching and Learning in Nigerian Universities in Northeast Nigeria - Umoru, Mohammed Lawal; Ibanga, Isaac John; Sunday, Philip (Darul Yasin Al Sys, 2024)
The main purpose of this study was to determine the attitude of vocational and technical education lecturers towards the utilization of Open Educational Resources for effective teaching and learning in Nigerian universities in northeast Nigeria. The study adopted a survey research design and was carried out in northeast Nigeria. The population of the study was 782 Vocational and Technical Education lecturers from 5 universities that offered Vocational and Technical Education in northeast, Nigeria. The study adopted Simple random sampling to select a sample size of 254 respondents using Krejcie and Morgan (1970) sample size table. Attitude of Teachers Towards Utilization of Open Educational Resources Questionnaire, (ATTUOER-Q) was used as a data collection instrument. The questionnaire was subjected to face validation and a reliability index of 0.91 was obtained using Cronbach Alpha. The data for the study was analyzed using mean and standard deviation to answer the research questions. The findings of the study revealed that the factors that influence VTE lecturers’ attitudes towards the utilization of OERs include technological infrastructure and readiness, educator capacity and awareness, and content quality and relevance among others; the study further revealed that to a high extent, lecturers in Nigerian universities are aware of OERs available for teaching and learning. The study recommended that Institutions should develop and implement comprehensive training programs specially tailored to the needs and conditions of vocational and technical education lecturers in Northeast Nigerian universities. And The National Council of Universities should recommend increased institutional support and resources to facilitate the integration of OER into vocational and technical education programs